PERAN LEMBAGA OTORITAS JASA KEUANGAN (OJK) DALAM MENGATASI PERUSAHAAN FINTECH LENDING ILEGAL - Sri Kusuma Wardhani Ida Ayu (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The existence of Fintech (financial technology) in Indonesia has grown since 2006, but Fintech Lending itself only first appeared in 2016 and continues to experience growth. Fintech Lending is a type of Fintech that is better known in Indonesian society, where from 2017 to 2021 the total Fintech Lending registered and licensed at OJK is as many as 104 companies. Fintech Lending is a method that can provide an alternative solution in the process of borrowing and borrowing money online with easier conditions and a faster process than conventional financial institutions, on the other hand problems arise due to the number of illegal Fintech Lending that has sprung up easily accessible to irresponsible and insecure people for their users, where July 2021 SWI has cracked down as many as 3,365 Fintech Lending has been illegal since 2018. The high number of Fintech Lending illegally rather than legally resulting in complex problems in practice in Indonesia that need to be addressed with regulatory regulations that include supervision, destruction and law enforcement. The role of OJK as a state institution to manage and supervise Fintech Lending has issued special rules regarding Fintech Lending through POJK Number 77 / POJK.01 / 2016 concerning Information Technology-Based Money Lending Services but in substance the law only applies to Fintech Lending which is legal only due to the absence of criminal provisions that ensnare Fintech Lending without permission. So see the existence of a legal vacuum (leenten van normen). Based on this background, the problems discussed in this study are as follows: 1) The Role of Financial Services Authority (OJK) Institutions in Overcoming Illegal Fintech Lending Companies? and 2) How is the Legal Effort of the Financial Services Authority (OJK) Institution in Overcoming Illegal Fintech Lending Companies? The research methods used are normative juridical research, using a statutory approach (statue approach) and a conceptual approach, techniques for collecting legal materials using primary legal materials and secondary legal materials, legal material analysis techniques used in this study are descriptive, comparative, evaluative, and argumentative. The results showed that the role of the Financial Services Authority (OJK) in overcoming Illegal Fintech Lending companies can currently only make efforts to close and block applications through the Investment Alert Task Force. This occurs due to two obstacles, namely internal barriers from the legal subsansi POJK Number 77 / POJK.01 / 2016 does not contain a detailed explanation related to how Fintech positions in the eyes of the law, the absence of regulations or special laws that give authority for OJK to follow up on illegal Fintech Lending. External barriers are still the lack of public legal awareness in knowledge, understanding attitudes, and legal behavior as illegal Fintech Lending users. The legal efforts that in overcoming illegal Fintech Lending companies today are with repressive legal efforts and preventive legal efforts.